Megaprojetos de hidrelétricas brasileiras: um olhar sobre responsabilidade social corporativa - Albuquerque, Marco André Fernandes (2013)
In a world where the issue regarding the necessity to protect the environment, and where the socially responsible movement is booming, this work came through as a result of the curiosity to understand the binomial economic development versus sustainable development. Aiming to understand how was this relationship evolution in great Brazilian hydroelectric projects. In this context, events surveys during the construction of the Itaipu Dam served as a comparative basis for what is being experienced today in the construction of the Santo Antônio Dam. The fact is that projects of this magnitude will cause impacts and externalities, but understanding how they are being treated is something that can guide the progress of these projects management. Therefore issues such as the preservation of fauna and flora, resettlement and local development, were put on the agenda to verify how today, even with the advance of technology and external pressures on the sustainability issue, the externalities of those projects are still same. The theories presented in Corporate Social Responsibility, sustainable and economic development, in addition to social movements structuring, will serve as basis for understanding the presented issues. It was identified that the sacrifice of a few for the enjoyment of others continues to be one of the main issues to be resolved, and in this we can include the land issue. As well as the non-integration between stakeholders and shareholders to achieve alignment on the best way to enjoy and interact with the environment in which the project will be inserted, the political exclusion of stakeholders on the decision-making process of hydropower projects to be implemented, are also identified.